VD_FINDINFO Jug / 2020 / 216 vom 30. September 2019 - VD Tribunal cantonal (2019)
VIOL, CONTRAINTE SEXUELLE, RESPONSABILITÉDROIT PÉNAL, EXPULSIONDROIT PÉNAL | 189 al. 1 CP, 19 CP, 190 al. 1 CP, 47 CP, 66a CP